2015
DOI: 10.1039/c5ob00184f
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic cucurbit[n]uril-type molecular containers: influence of glycoluril oligomer length on their function as solubilizing agents

Abstract: We present the synthesis of a series of six new glycoluril derived molecular clips and acyclic CB[n]-type molecular containers (1 – 3) that all feature SO3− solubilizing groups but differ in the number of glycoluril rings between the two terminal dialkoxyaromatic sidewalls. We report the x-ray crystal structure of 3b which shows that its dialkoxynaphthalene sidewalls actively define a hydrophobic cavity with high potential to engage in π–π interactions with insoluble aromatic guests. Compounds 1 – 3 possess ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 100 publications
1
58
0
Order By: Relevance
“…Compound 1 was prepared as described previously. [20] Figure 2b,c shows two views of the electrostatic potential surface of an MMFF model of 1 . As expected, the ureidyl C=O groups of the glycoluril building blocks are regions of highly negative electrostatic potential (≈ −200 kcal mol −1 ) due to the convergence of the neighboring C=O groups and the four SO 3 − groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 1 was prepared as described previously. [20] Figure 2b,c shows two views of the electrostatic potential surface of an MMFF model of 1 . As expected, the ureidyl C=O groups of the glycoluril building blocks are regions of highly negative electrostatic potential (≈ −200 kcal mol −1 ) due to the convergence of the neighboring C=O groups and the four SO 3 − groups.…”
Section: Resultsmentioning
confidence: 99%
“…camptothecin and PBS-1086) although not as potently as M2 . [20] Around this time we were approached by the organizers of the SAMPL5 challenge who requested a blinded data set of host•guest binding constants. [14] Given the earlier use of macrocyclic CB[n] and acyclic CB[n]–type containers in the SAMPL challenges [14,15] it seemed appropriate to study the host-guest recognition properties of glycoluril dimer molecular clip 1 for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the internal molecular recognition surfaces of acyclic CB[n] can be tailored by synthetic modifications. In a series of papers, we have explored the influence of the nature of the solubilizing groups, 38 the aromatic walls, 37 and the length of the central glycoluril oligomer 39 on the solubilizing ability of acyclic CB[n]-type containers. We have found that acyclic CB[n] display higher binding affinity (range: 10 3 – 10 6 M −1 ) than HP-β-CD (range: 10 2 – 10 4 M −1 ) toward a panel of 19 insoluble drugs which means that lower concentrations of acyclic CB[n] are needed to formulate a given concentration of drug.…”
Section: Introductionmentioning
confidence: 99%
“…It has three characteristic structural features; (1) a central glycoluril oligomer induces curvature, (2) terminal aromatic walls enhance binding to drugs with aromatic rings, and (3) sulfonate arms enhance solubility [40, 41]. The Isaacs group measured the binding affinities CBClip and ten guest molecules.…”
Section: Introductionmentioning
confidence: 99%